White Cart Loom. Issue 2 (1st December 2017) - Isley, Vicky; Smith, Paul
British artists Vicky Isley and Paul Smith (collectively known as boredomresearch) were commissioned in 2016 by the University of the West of Scotland (UWS) to produce a new digital artwork with the aim of supporting Paisley's bid to be City of Culture 2021. The commission was co-funded by UWS and Renfrewshire Council, Scotland. The resulting artwork titled White Cart Loom weaves a narrative combining Paisley's rich industrial past with current scientific and ecological work, fighting to save a rare organism from extinction.